The Influence of Multicultural Values in Civics Education on MI Students' Tolerance and Nationalism - Riris Fatimah Nur Jannah; Murfiah Dewi Wulandari (Elementary Teacher Education Program, Majalengka University, 2025)
Learning in Madrasah Ibtidaiyah or elementary schools prioritizes character education, which can be obtained in various ways, one is through the approach of multicultural values ​​in PPKn learning. This study aims to empirically test the influence of multicultural values ​​in PPKn learning on the behavior of tolerance and love of the homeland in students of Madrasah Ibtidaiyah (MI) Muhammadiyah Bloran located in Kerjo District, Karanganyar Regency, Central Java Province, which has implemented Pancasila and Citizenship Education (PPKN) learning in Unit 3 with the title